Development of a prebiotic strawberry preparation for the dairy industry - Gonçalves, D. A. (2022)
Background. Food industry has been pressed to develop products with reduced sugar and caloric value, with the challenge of keeping rheological and sensory characteristics. Herein we developed a functional strawberry preparation for the dairy industry, by in-situ enzymatic conversion of sucrose into prebiotic fructo-oligosaccharides (FOS). Methodology. Two enzymatic complexes (Pectinex®Ultra SP-L and Viscozyme®L) were applied in the preparation. Operational parameters were optimized to maximize FOS yield: temperature, pH, enzyme:substrate ratio (E/S). Rheological, physicochemical and functional properties (INFOGEST gastrointestinal digestion protocol) were evaluated. Results. At optimal conditions (60 , pH 5.0), Pectinex produced 265±3 g·L1 FOS, yielding 0.581±0.006 gFOS·gin.GF1 after 7 h reaction (E/S:1/40); and Viscozyme produced 295±1 g·L1 FOS, yielding 0.664±0.004 gFOS·gin.GF1 after 5 h (E/S:1/30), both resulting in preparations with 50% (w/w) FOS. The caloric value was reduced 24%, including 80% sucrose reduction. Differences in colour, water activity and ºBrix were not relevant, while consistency and viscosity decreased 70% and pH increased from 4.4 to 4.7. FOS showed resistance to gastrointestinal digestion; only kestose was slightly hydrolysed at intestinal phase. Conclusions. A prebiotic strawberry preparation was successfully produced at lab scale, by in-situ enzymatic conversion of caloric into functional sugars. Next, the process will be scaled-up at industrial level. Background. Food industry has been pressed to develop products with reduced sugar and caloric value, with the challenge of keeping rheological and sensory characteristics. Herein we developed a functional strawberry preparation for the dairy industry, by in-situ enzymatic conversion of sucrose into prebiotic fructo-oligosaccharides (FOS). Methodology. Two enzymatic complexes (Pectinex®Ultra SP-L and Viscozyme®L) were applied in the preparation. Operational parameters were optimized to maximize FOS yield: temperature, pH, enzyme:substrate ratio (E/S). Rheological, physicochemical and functional properties (INFOGEST gastrointestinal digestion protocol) were evaluated. Results. At optimal conditions (60 , pH 5.0), Pectinex produced 265±3 g/L FOS, yielding 0.581±0.006 g(FOS)/g(initial.GF) after 7 h reaction (E/S:1/40); and Viscozyme produced 295±1 g/L FOS, yielding 0.664±0.004 g(FOS)/g(initial.GF) after 5 h (E/S:1/30), both resulting in preparations with 50% (w/w) FOS. The caloric value was reduced 24%, including 80% sucrose reduction. Differences in colour, water activity and ºBrix were not relevant, while consistency and viscosity decreased 70% and pH increased from 4.4 to 4.7. FOS showed resistance to gastrointestinal digestion; only kestose was slightly hydrolysed at intestinal phase. Conclusions. A prebiotic strawberry preparation was successfully produced at lab scale, by in-situ enzymatic conversion of caloric into functional sugars. Next, the process will be scaled-up at industrial level.